Abrupt transformation of West Greenland lakes following compound climate extremes associated with atmospheric rivers - Jasmine E. Saros; Václava Hazuková; Robert M. Northington; Grayson P. Huston; Avery Lamb; Sean Birkel; Ryan Pereira; Guillaume Bourdin; Binbin Jiang; Suzanne McGowan (Proceedings of the National Academy of Sciences, 2025)
Arctic ecosystems are affected by accelerated warming as well as the intensification of the hydrologic cycle, yet understanding of the impacts of compound climate extremes (e.g., simultaneous extreme heat and rainfall) remains limited, despite their high potential to alter ecosystems. Here, we show that the aquatic ecosystems in historically arid West Greenland have undergone an ecological transformation after a series of atmospheric rivers that simultaneously produced record heat and rainfall hit the region in autumn 2022. We analyzed a unique, long-term lake dataset and found that compound climate extremes pushed Arctic lakes across a tipping point. As terrestrial–aquatic linkages were strengthened, lakes synchronously transformed from “blue” lakes with high transparency and low pelagic primary production to “brown” in less than a year, owing to a large influx of dissolved organic material and metals, with iron concentrations increasing by more than two orders of magnitude. The browning of lake waters reduced light penetration by 50% across lakes. The resulting light limitation altered plankton distributions and community structure, including a major reduction in prokaryotic diversity and an increase in algal groups capable of metabolizing organic carbon sources. As a result, lakes shifted from being summer carbon sinks to sources, with a >350% increase in carbon dioxide flux from lakes to the atmosphere. The remarkably rapid, coherent transformation of these Arctic ecosystems underscores the synergistic and unpredictable impacts of compound extreme events and the importance of their seasonal timing, especially in regions with negative moisture balance.